A novel PLA high oxygen barrier multilayer film/foam. (14th November 2022) - de Souza, Claudio Roberto Lima; Feng, Jingxing; Olah, Andrew; Baer, Eric; Mauler, Raquel Santos; Wnek, Gary
Abstract: Production of biopolymer for packaging applications is still a burgeoning demand with the rising environmental concern about pollution due to non‐degradable plastic waste materials. This paper introduces a novel approach, yet a continuous production method, to produce PLA multilayer film/foams structures having 16, 32, and 64 alternating layers which were developed by multilayer coextrusion technique, and the morphology, density, mechanical properties and oxygen transmission of the as‐extruded film/foams were characterized. The lightweight multilayered PLA film/foam has a unique solid/porous alternating horizontal architecture, in which the film layers can effectively control the growth of the cells and suppress the premature rupture of cells during coextrusion process. Tensile properties at elevated temperatures of the PLA film/foam were used to optimize thermoforming conditions. The effects of annealing temperature and time on the crystallinity and oxygen permeability of PLA multilayer film/foams were investigated. Oxygen transmission showed a strong correlation with the crystallinity of PLA multilayer film/foam. The material with 32 layers 50/50 film/foam achieved extremely high barrier after 30 min annealing, which is 35 times better than the control. Abstract : PLA Film/Foam multilayer coextrusion process.